Promoting nurse‐led behaviour change interventions to prevent cardiovascular disease in disadvantaged communities: A scoping review. (13th June 2022) - Freeley, Sarah; Broughan, John; McCombe, Geoff; Casey, Mary; Fitzpatrick, Patricia; Frawley, Timothy; Morrisey, Janis; Treanor, J. T.; Collins, Tim; Cullen, Walter
Abstract: Cardiovascular diseases (CVD) are the leading cause of death worldwide and they disproportionally affect people living in disadvantaged communities. Nurse‐led behaviour change interventions have shown great promise in preventing CVD. However, knowledge regarding the impact and nature of such interventions in disadvantaged communities is limited. This review aimed to address this knowledge gap. A six‐stage scoping review framework developed by Arksey and O'Malley, with revisions by Levac et al., was used. The search process was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses‐Extension for Scoping Reviews (PRISMA‐ScR). Three electronic databases were searched (PUBMED/MEDLINE, CINAHL Plus, and Cochrane CENTRAL), and included studies were analysed using Braun and Clarke's 'Thematic Analysis' approach. Initial searches yielded 952 papers and 30 studies were included in the review following duplicate, title/abstract, and full‐text screening. The included studies indicate that nurse‐led behaviour change primary prevention interventions in disadvantaged areas are largely effective; albeit the considerable variety of intervention approaches, study populations and outcome measures used to date make it difficult to ascertain this. Other identified key areas in the promotion of nurse‐led behaviour change included tailoring interventions to specific populations, providing adequate training for nurses, overcoming patient access difficulties and encouraging patient engagement. Overall, the findings indicate that nurse‐led behaviour change interventions for high‐risk CVD patients in disadvantaged areas show much promise, although there is considerable variety in the interventions employed and studied to date. Further research is needed to examine the unique barriers and facilitators of interventions for specific disadvantaged groups.